DEVELOPMENT OF MEDICAL CULTURE IN THE FAMILY (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article shows the importance of developing a medical culture in the family and its role in health care. Basic aspects such as establishing a healthy lifestyle in the family, increasing medical knowledge, proper use of medical services and creating a healthy environment are discussed. It is also emphasized the need to increase responsibility in health care matters through family unity and mutual support, and to teach children and adolescents a healthy lifestyle. The development of medical culture serves to improve not only individual health, but also the general well-being of society.